Analysis of Learning Motivation and Engagement of Physics Education Students in Self-Determination Theory-Based Learning - Lestari, Vika Bunga; Arinanti, Adinda; Khusna, Jihan Zahratul; Patma, Salwa; Susanti, Nova (Universitas Muhammadiyah Purworejo, 2026)
This study aims to analyze the learning motivation and engagement of PhysicsEducation students in Self-Determination Theory (SDT)-based learning. Thestudy used a descriptive quantitative design involving 76 students selectedthrough a total sampling technique. Data were collected using a 5-point Likertscale questionnaire consisting of 16 statements regarding student learningmotivation and engagement. Data analysis was carried out descriptively andusing a Pearson correlation test. The results showed that learning motivation wasin the high category with an average of 27.29 out of a maximum score of 35, andstudent engagement was also in the high category with an average of 34.79 out ofa maximum score of 45. The majority ofstudentsresponded positively to indicatorsof autonomy, competence, connectedness, as well as behavioral, emotional, andcognitive engagement. These findings indicate that SDT-based digital learningcan increase students' intrinsic motivation and active participation.Keywords: Learning motivation, engagement, Self-Determination Theory,digital learning, physics education